Transfer and priming of surgical skills across minimally invasive surgical platforms - Zihni, Ahmed; Ge, Tianjia; Ray, Shuddhadeb; Wang, Robert; Liang, Zhe; Cavallo, Jaime A.; Awad, Michael M. (The Journal of surgical research, 2016)
Robot-assisted laparoscopic surgery (RALS) uses 3-dimensional visualization and wristed instruments that provide more degrees of freedom than rigid traditional laparoscopic (TLS) instrumentation. These features have been touted to improve accuracy and efficiency during surgical task performance. Little is known, however, about the transferability of skills between the two platforms or whether task performance on one platform primes surgeons for task performance on the other. Twenty-six subjects naïve to RALS were recruited to perform three Fundamentals of Laparoscopic Surgery tasks on both TLS and RALS platforms: peg transfer, pattern cutting (PC), and intracorporeal suturing. All tasks were performed within Fundamentals of Laparoscopic Surgery testing parameters and repeated three times by each subject on each platform. Platform and task order were randomized. Errors in task performance were defined as drops in the peg transfer task, faults 5 mm or more from the defined pattern during PC, and faults greater than 1 mm in suture placement from the defined points in intracorporeal suturing. Mean completion times and mean errors per trial (EPT) were calculated for each task on both platforms. Results were compared between those who performed TLS first (LF) and those who performed RALS first (RF) using unpaired Student's t-test (P < 0.05 considered statistically significant). No statistically significant differences in task completion time were noted between the LF and RF groups. RF subjects had fewer errors during robotic PC than LF subjects (1.02 EPT versus 1.86 EPT, respectively; P = 0.02). No other differences in task quality were noted. In surgeon's naïve to RALS, there is no evidence that skills acquired on RALS or TLS platforms are transferable to the other platform or that performing tasks on one platform primes a subject for task performance on the other. Performing TLS PC may have had a negative impact on subsequent RALS PC performance. These findings suggest that distinct programs for skills acquisition are necessary for both the TLS and RALS platforms.